Expression, Purification And Characterization Of Organic Solvent Tolerant Lipase From Bacillus Sphaericus 205y - Sulong, Moohamad Ropaning (2005)
One thousand and two hundred base pairs (bp) of open reading frame (ORF) encoding for an organic solvent tolerant lipase gene was cloned and expressed intra- and extracellularly. The intracellular expression was done using pBAD TOPO TA expression vector with 0.02% (vlv) of L-arabinose as optimum inducer after 4 h of incubation. at 37°C with an optimum lipase activity of 0.5 Ulml. The extracellular expression was obtained by cotransforming pJL3 expression vector encoding bacteriocin release protein (BRP) into E. coli TOP10 harbouring the recombinant pBAD TOPO TA. The secretory expression of recombinant organic solvent tolerant 205y lipase increased the lipase activity tremendously to 2.5 Ulml. The 205y lipase was purified to 8-fold and 32% recovery using two steps purification, ultrafiltration and hydrophobic interaction chromatography (HIC). The molecular mass of the purified 205y lipase revealed homogeneity on SDS-PAGE at approximately 30 kDa. The optimum pH for the purified 205y lipase was found at 7.0-8.0 and its stability showed a broad range of pH value between pH 5.0 to pH 13.0 at 37 "C. The purified 205y lipase exhibited an optimum temperature of 55°C. The lipase activity of the purified 205y lipase was enhanced in the presence of alkaline metal such as (Na) and alkaline earth metal such as ( ~ g ~c'a,2 ' and ~ a ~ ' )H.o wever, the 205y lipase activity was inhibited in the presence of transition metal ions, zn2', cu2' and ~ e ~ 'T.h e chelating agent, ethylenediaminetetraacetic acid (EDTA), did not affect the purified 205y lipase activity while serine hydrolase inhibitor, phenylmethane sulfonoyl fluoride (PMSF), inhibited the lipase activity. The activity of the purified 205y lipase demonstrated good stability in the presence of methanol, p-xylene and n-decane with Dimethylsulfoxide (DMSO) being the most stabilizing. The purified 205y lipase showed a preference toward hydrolysing medium carbon chain length of triglycerides, tricaprin (C10). The purified 205y lipase also exhibited 1,3- regiospecific nature of the enzyme.